EFFORTS TO IMPROVE ACTIVITIES AND MATHEMATICS LEARNING OUTCOMES THROUGH APPLICATION OF CONTEXTUAL METHODS TO STUDENTS: Indonesia - Sukiyah, Sukiyah (STIT Pringsewu, 2023)
ABSTRACT This class action research (CAR) aims to improve the mathematics learning outcomes of class VI UPT SDN 1 Pardasuka students. The research was carried out in two cycles each consisting of two meetings through the following stages: planning, observation and reflection. Data collection techniques were carried out through observation sheets at each meeting by observers to view data on learning activities, while data on learning outcomes were obtained through daily test scores and students' mathematics learning achievements in cycle 1 and cycle 2. The results obtained from Classroom Action Research (PTK) through the contextual method model, show an increase in the results of student activities, especially in activities for preparing places, materials and tools by 55.56%, activities for expressing ideas by 66.67% and for activities reading contextual rules and books experienced 74.04%. Based on data on students' mathematics learning achievement, the class average value in cycle I was 69.62, increasing to 73.51 in cycle II. The percentage of students who reached the standard of completeness also increased in cycle I by 88.88% (Good Category), increased to 100% (Special Category) in cycle II. Keywords: Contextual Method, Learning Activities, Mathematics Learning Outcomes